Pendekatan Interaktif dalam Edukasi Menabung untuk Meningkatkan Literasi Keuangan Siswa di SDN 338 Pasaka - Fuji Pratiwi; Muzakkir; Nurwahyudi; Dermawan (YP-SDI Lamaddukelleng, 2024)
The formation of the habit of saving at an early age is of significant importance with regard to the long-term management of personal finances. This research project, conducted with students at SDN 338 Pasaka, explores the advantages of instilling savings habits in children, including the development of discipline, responsibility, and an understanding of the value of money. Furthermore, the text outlines effective pedagogical strategies that parents and educators can employ in teaching children about the importance of saving. These include providing hands-on examples, making piggy banks, and planning simple financial goals. By saving early, children not only learn to manage money wisely but are also prepared to face financial challenges in adulthood.